Composition for transmission belt

By using copolymers containing ethylene, α-olefins and non-conjugated polyenes in the conveyor belt, and adding carbon black and staple fibers, the problems of insufficient adhesion strength and poor thermal aging performance of the copolymer are solved, and high-efficiency molding and good thermal aging performance are achieved.

JP2025044142APending Publication Date: 2025-04-01MITSUI CHEMICALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024146810
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-19
Filing Date
2024-08-28
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When using ethylene-propylene-nonconjugated polyene copolymer, the adhesion strength (tack) between the conveyor belt components is insufficient, resulting in difficult forming and processing. In addition, the performance of the conveyor belt under thermal aging and low temperature conditions is poor.

Method used

Copolymers containing ethylene, α-olefins (with 4 to 20 carbon atoms) and non-conjugated polyenes are used, and carbon black and staple fibers are added thereto, so that the thermal aging resistance and processing properties of the copolymer are improved by adjusting the structural unit ratio and molecular structural characteristics of the copolymer.

Benefits of technology

High adhesion strength between conveyor belt components is achieved, feasibility of forming processing is improved, and a good performance balance is maintained under thermal aging and low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044142000001
    Figure 2025044142000001
  • Figure 2025044142000002
    Figure 2025044142000002
  • Figure 2025044142000003
    Figure 2025044142000003
Patent Text Reader

Abstract

To provide a composition for a transmission belt excellent in processability and thermal aging resistance and excellent in balance between modulus and elongation.SOLUTION: The composition for a transmission belt contains: an ethylene / α-olefin / nonconjugated polyene copolymer (A) which has a structural unit derived from ethylene [A1], a structural unit derived from a C4-20 α-olefin [A2], and a structural unit derived from a nonconjugated polyene [A3] containing two or more partial structures selected from the group consisting of the following general formulae (I) and (II) in total in the molecule and satisfies specific requirements (1)-(4), the structural unit derived from the C4-20 α-olefin [A2] containing a structural unit derived from 1-butene, and the structural unit derived from the nonconjugated polyene [A3] containing a structural unit derived from 5-vinyl-2-norbornene; carbon black (B); and short fibers (C).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for a power transmission belt. [Background technology]

[0002] Power transmission belts are widely used in automobiles, motorcycles, and general industrial machines. Power transmission belts are required to have high rubber elasticity and abrasion resistance. Chloroprene rubber is usually used to manufacture power transmission belts that satisfy the above properties. However, due to the demand for improved heat resistance and cold resistance, and for weight reduction, the use of ethylene-α-olefin-non-conjugated polyene copolymer rubber instead of chloroprene rubber has been investigated (for example, see Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-310951 A [Patent Document 2] JP 2012-215212 A Summary of the Invention [Problem to be solved by the invention]

[0004] According to the investigations of the present inventors, when an ethylene-propylene-non-conjugated polyene copolymer is used, the adhesive strength (tack) between sheets formed from a composition for a transmission belt containing the copolymer tends to be insufficient, and therefore molding processing tends to be difficult. An object of the present invention is to provide a composition for a transmission belt which is excellent in processability and heat aging resistance and has an excellent balance between modulus and elongation. [Means for solving the problem]

[0005] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above problems can be solved by the following embodiments, and have completed the present invention.

[0006] [1] A polymer having a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in the molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfying the following requirements (1) to (4): the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms contains a structural unit derived from 1-butene, an ethylene-α-olefin-non-conjugated polyene copolymer (A), in which the structural units derived from the non-conjugated polyene [A3] include structural units derived from 5-vinyl-2-norbornene; Carbon black (B); and (C) short fibers. [ka] Requirement (1): The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 40 / 60 to 90 / 10; Requirement (2): the content of structural units derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of structural units derived from ethylene [A1], the α-olefin [A2] having 4 to 20 carbon atoms, and the non-conjugated polyene [A3]; Requirement (3): The B value represented by the following formula (i) is 1.20 or more; B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii): BrNo≧0.5 …Formula (ii) [2] The composition for a transmission belt according to item [1], wherein the ethylene-α-olefin-non-conjugated polyene copolymer (A) satisfies one or more of the following requirements (5) to (8): Requirement (5): the weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (wt%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii); 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 … Formula (iii) Requirement (6): Complex viscosity η at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurement (190 °C) using a rheometer * ( ω =0.1) (Pa sec) and the complex viscosity η at frequency ω = 100 rad / s * ( ω =100) (Pa sec) P〔η * ( ω =0.1) / η * ( ω =100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of [A3] satisfy the following formula (iv); P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 6 … Formula (iv) Requirement (7): Complex viscosity η at frequency ω = 0.01 rad / s obtained by linear viscoelastic measurement (190 °C) using a rheometer * ( ω =0.01) (Pa sec) and the complex viscosity η at frequency ω=10rad / s * ( ω =10) (Pa sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v). Log{η * ( ω =0.01)} / Log{η * ( ω =10)}≦0.0753×{non-conjugated polyene [A3] derived apparent iodine value} + 1.42 … formula (v) Requirement (8): The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is -65°C or lower. [3] The composition for a transmission belt according to item [1] or [2], wherein the content of the short fibers (C) is 0.1 to 100 parts by mass per 100 parts by mass of the copolymer (A). [4] The composition for a transmission belt according to any one of items [1] to [3], wherein the short fibers (C) are aramid fibers. [5] The composition for a transmission belt according to any one of items [1] to [4], wherein the copolymer (A) has a Mooney viscosity ML(1+4)100°C of 5 to 150. [6] The composition for a transmission belt according to any one of items [1] to [5], further comprising an organic peroxide as a crosslinking agent (D). [7] The composition for a transmission belt according to any one of items [1] to [6], further comprising 0.1 to 20 parts by mass of a processing aid (E) based on 100 parts by mass of the copolymer (A). [8] The composition for a transmission belt according to any one of items [1] to [7], further comprising a crosslinking auxiliary (F). [9] The composition for a transmission belt according to any one of items [1] to [8], further comprising trans-polyoctenylene.

[10] The composition for a transmission belt according to any one of items [1] to [9], further comprising a modified polybutadiene.

[11] A molded article formed from the composition for a transmission belt according to any one of items [1] to

[10] .

[12] A power transmission belt having the molded article according to item

[11] .

[13] A crosslinked molded article formed from the composition for a transmission belt according to any one of items [1] to

[10] .

[14] A power transmission belt having the crosslinked molded article according to item

[13] . Effect of the Invention

[0007] According to the present invention, it is possible to provide a composition for a power transmission belt which is excellent in processability and heat aging resistance, and has an excellent balance between modulus and elongation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below.

[0009] [Composition for transmission belts] The composition for a power transmission belt of the present invention (hereinafter also referred to as "the composition of the present invention") contains an ethylene-α-olefin-non-conjugated polyene copolymer (A), carbon black (B) and short fibers (C) described below.

[0010] <Ethylene-α-olefin-non-conjugated polyene copolymer (A)> The ethylene-α-olefin-non-conjugated polyene copolymer (A) (hereinafter also referred to as "copolymer (A)"), which is one of the components of the composition of the present invention, has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing in the molecule a total of two or more partial structures selected from the group consisting of the following general formulas (I) and (II), and satisfies the following requirements (1) to (4): the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms contains a structural unit derived from 1-butene, The structural units derived from the non-conjugated polyene [A3] include structural units derived from 5-vinyl-2-norbornene.

[0011] [ka]

[0012] Requirement (1): The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 40 / 60 to 90 / 10. Requirement (2): The content of structural units derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of structural units derived from ethylene [A1], the α-olefin [A2] having 4 to 20 carbon atoms, and the non-conjugated polyene [A3]. Requirement (3): The B value represented by the following formula (i) is 1.20 or more. B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii): BrNo≧0.5 …Formula (ii)

[0013] Examples of the α-olefins [A2] having 4 to 20 carbon atoms include 1-butene, 1-nonene, 1-decene, 1-nonadecene, 1-eicosene, and the like, which have a linear structure without a side chain; and 4-methyl-1-pentene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, and the like, which have a side chain.

[0014] These α-olefins [A2] may contain 1-butene, and may be used alone or in combination of two or more kinds containing 1-butene. When the α-olefin [A2] is used in combination with 1-butene, among these, α-olefins having 4 to 10 carbon atoms are preferred, and 1-hexene and 1-octene are more preferred.

[0015] Ethylene-propylene-non-conjugated polyene copolymers, in which the α-olefin is propylene, have insufficient rubber elasticity at low temperatures, so their applications may be limited. On the other hand, copolymer (A) has structural units derived from α-olefins [A2] with 4 to 20 carbon atoms, so it has excellent rubber elasticity at low temperatures.

[0016] Examples of the non-conjugated polyene [A3] containing, in the molecule, two or more partial structures selected from the group consisting of the general formulae (I) and (II) include 5-vinyl-2-norbornene (VNB), norbornadiene, 1,4-hexadiene, and dicyclopentadiene.

[0017] VNB is highly available, has good crosslinking properties with organic peroxides, and is likely to improve the heat resistance of the copolymer composition. The non-conjugated polyene [A3] may contain VNB, and may be used alone or in combination of two or more types containing VNB, but it is preferable to use VNB alone.

[0018] The copolymer (A) according to the present invention may contain, in addition to structural units derived from ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2], and the non-conjugated polyene [A3], a structural unit derived from a non-conjugated polyene [A4] containing only one partial structure selected from the group consisting of the general formulae (I) and (II) in the molecule.

[0019] Examples of such non-conjugated polyenes [A4] include 5-ethylidene-2-norbornene (ENB), 5-methylene-2-norbornene, 5-(2-propenyl)-2-norbornene, 5-(3-butenyl)-2-norbornene, 5-(1-methyl-2-propenyl)-2-norbornene, 5-(4-pentenyl)-2-norbornene, 5-(1-methyl-3-butenyl)-2-norbornene, 5-(5-hexenyl)-2-norbornene, 5-(1-methyl-4-pentenyl)-2-norbornene, 5-(2,3-dimethyl-3-butenyl)-2-norbornene, 5-(2-ethyl-3-butenyl)-2-norbornene, 5-(1,2-dimethyl-5-hexenyl)-2-norbornene, 5-(5-ethyl-5-hexenyl)-2-norbornene, 5-(1,2,3-trimethyl-4-pentenyl)-2-norbornene, 5-(6-heptenyl)-2-norbornene, 5-(3-methyl-5-hexenyl)-2-norbornene, 5-(3,4-dimethyl-4-pentenyl)-2-norbornene, 5-(3-ethyl-4-pentenyl)-2-norbornene, 5-(7-octenyl)-2-norbornene, 5-(2-methyl-6-heptenyl)-2-norbornene, 5-(1,2-dimethyl-5-hexenyl)-2-norbornene, 5-(5-ethyl-5-hexenyl)-2-norbornene, 5-(1,2,3-trimethyl-4-pentenyl)-2-norbornene, and the like. Among these, ENB is preferred because it is easily available, the crosslinking rate during crosslinking with an organic peroxide is easily controlled, and good mechanical properties are easily obtained. The non-conjugated polyene [A4] may be used alone or in combination of two or more kinds.

[0020] The copolymer (A) may contain at least one or more biomass-derived monomers (ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, non-conjugated polyenes [A3], and non-conjugated polyenes [A4]). Examples of biomass-derived α-olefins include biomass-derived 1-butene. Examples of biomass-derived non-conjugated polyenes include biomass-derived 5-vinyl-2-norbornene. The monomers that are the raw materials for the copolymer (A) may contain only biomass-derived monomers, or may contain both biomass-derived monomers and fossil fuel-derived monomers. Note that biomass-derived monomers such as biomass-derived ethylene, biomass-derived α-olefins, and biomass-derived non-conjugated polyenes can be obtained by known methods. It is preferable that the copolymer (A) contains a structural unit derived from a biomass-derived monomer from the viewpoint of reducing environmental load.

[0021] Each of the copolymers (A) may contain at least one or more constituent units derived from chemically recycled monomers. The chemically recycled monomers used as raw materials for the copolymer (A) may be ethylene derived from chemically recycled, α-olefins derived from chemically recycled, or non-conjugated polyenes derived from chemically recycled. Furthermore, the monomers used as raw materials for the copolymer (A) may contain only monomers derived from chemically recycled, or may contain both monomers derived from chemically recycled and monomers derived from fossil fuels. Note that chemically recycled monomers such as ethylene derived from chemically recycled, α-olefins derived from chemically recycled, and non-conjugated polyenes derived from chemically recycled can be obtained by known methods. It is preferable for the copolymer (A) to contain a structural unit derived from a chemically recycled monomer from the viewpoint of reducing the environmental load (mainly reducing waste).

[0022] Requirement (1) The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms is 40 / 60 to 90 / 10. The copolymer (A) having a molar ratio within the above range has an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature.

[0023] The lower limit of the molar ratio [A1] / [A2] is preferably 45 / 55, more preferably 50 / 50, even more preferably 55 / 45, and particularly preferably 60 / 40. The upper limit of the molar ratio [A1] / [A2] is preferably 80 / 20, more preferably 75 / 25, even more preferably 70 / 30, and particularly preferably 68 / 32.

[0024] Requirement (2) The content of the structural unit derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % based on the total of the structural unit derived from ethylene [A1], the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms, and the structural unit derived from the non-conjugated polyene [A3] being 100 mol %. The copolymer (A) having this content in the above range has sufficient crosslinkability and flexibility. In this specification, the content of each structural unit in the resin can be measured by NMR spectrum or the like.

[0025] The lower limit of the content of the structural unit derived from the non-conjugated polyene [A3] is preferably 0.2 mol%. The upper limit of the content of the structural unit derived from the non-conjugated polyene [A3] is preferably 4.0 mol%, more preferably 3.5 mol%, further preferably 3.0 mol%, particularly preferably 2.5 mol%. When the content of the structural unit derived from the non-conjugated polyene [A3] is within the above range, a copolymer (A) having sufficient crosslinkability and flexibility can be obtained.

[0026] Requirement (3) The B value represented by the following formula (i) is 1.20 or more, preferably in the range of 1.20 to 1.80, more preferably 1.25 to 1.60, still more preferably 1.30 to 1.45, and particularly preferably 1.35 to 1.45. B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.] An ethylene copolymer having a B value of less than 1.20 exhibits a large compression set at low temperatures, and it may not be possible to obtain an ethylene copolymer having an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature.

[0027] The B value is an index showing the randomness of the copolymerization monomer sequence distribution in the copolymer (A), and [E], [X], [Y], and [EX] in the formula (i) are 13 The amount of carbon ions can be determined by measuring the C-NMR spectrum, based on the reports of JC Randal [Macromolecules, 15, 353 (1982)] and J. Ray [Macromolecules, 10, 773 (1977)].

[0028] Requirement (4) The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii). BrNo≧0.5 …Formula (ii) Here, the number of branch points per molecular chain, BrNo, can be determined by a structural analysis method using 3D-GPC. In this specification, specifically, it was determined as described in the examples described later.

[0029] The copolymer (A) more preferably satisfies the following formula (ii-1). BrNo≧0.8 …Formula (ii-1) It is preferable that the number of branching points per molecular chain satisfies the above formula (ii) or (ii-1), because when a crosslinked molded article is produced, the crosslinking rate is excellent and the molded article after crosslinking exhibits excellent mechanical properties.

[0030] The copolymer (A) more preferably satisfies the following formula (ii-2). 3.0≧BrNo …Formula (ii-2) It is preferable that the number of branching points per molecular chain satisfies the above formula (ii-2), since the compression set at low temperatures is small and the balance between rubber elasticity at low temperatures and tensile strength at room temperature is excellent.

[0031] The copolymer (A) according to the present invention preferably satisfies any one or more of the following requirements (5) to (8), more preferably satisfies three or more requirements, and further preferably satisfies all four requirements.

[0032] Requirement (5) The weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (wt%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii): 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 … Formula (iii)

[0033] When the copolymer (A) according to the present invention satisfies the requirement (5), a non-conjugated polyene such as VNB can be used. The content of the structural unit derived from [A3] is appropriate, and sufficient crosslinking performance is exhibited. In addition, when a crosslinked molded article is produced using the copolymer (A) according to the present invention, the crosslinking rate is excellent and the molded article after crosslinking exhibits excellent mechanical properties, which is preferable.

[0034] The copolymer (A) according to the present invention more preferably satisfies the following formula (iii-1). 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦60 … Formula (iii-1)

[0035] The copolymer (A) according to the present invention more preferably satisfies the following formula (iii-2). 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦35 … Formula (iii-2)

[0036] The weight average molecular weight (Mw) of the copolymer (A) can be determined as a polystyrene-equivalent value measured by gel permeation chromatography (GPC). In this specification, specifically, it is determined by using 3D-GPC as described in the examples described later.

[0037] The copolymer (A) according to the present invention has an appropriate degree of crosslinking when the "Mw × weight fraction of [A3] / 100 / molecular weight of [A3]" satisfies the above formula (iii), (iii-1) or (iii-2), and by using this copolymer, a transmission belt having excellent mechanical properties and heat aging resistance in a well-balanced manner can be produced.

[0038] Requirement (6) Complex viscosity η at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurements (190 °C) using a rheometer * ( ω =0.1) (Pa sec) and the complex viscosity η at frequency ω = 100 rad / s * ( ω =100) (Pa sec) P〔η * ( ω =0.1) / η * ( ω =100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of [A3] satisfy the following formula (iv). P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 6 … Formula (iv)

[0039] Here, the complex viscosity η at frequency ω=0.1rad / s * ( ω =0.1) and the complex viscosity η at frequency ω=100rad / s * ( ω =100) Ratio of P〔η * ( ω =0.1) / η * ( ω =100)] represents the frequency dependence of viscosity, and corresponds to the left side of the formula (iv) P / ([η] 2.9 ) tends to show high values ​​when there are a lot of long chain branches, although it is affected by short chain branches, molecular weight, etc.

[0040] Generally, in an ethylene-α-olefin-non-conjugated polyene copolymer, the more structural units derived from non-conjugated polyenes the copolymer contains, the more long chain branches it tends to contain. However, it is considered that the copolymer (A) according to the present invention has fewer long chain branches than the conventionally known ethylene-α-olefin-non-conjugated polyene copolymers, and therefore can satisfy the above formula (iv).

[0041] In the present invention, the P value is determined by performing measurements using a viscoelasticity measuring device Ares (manufactured by Rheometric Scientific) at 190° C., strain 1.0%, and various frequencies, and is calculated as the ratio (η * The ratio of

[0042] The copolymer (A) according to the present invention preferably satisfies the following formula (iv-1). P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 5.7 … Formula (iv-1) The intrinsic viscosity [η] of the copolymer (A) means a value measured in decalin at 135°C.

[0043] Requirement (7) Complex viscosity η at frequency ω = 0.01 rad / s obtained by linear viscoelastic measurements (190 °C) using a rheometer * ( ω =0.01) (Pa sec) and the complex viscosity η at frequency ω=10rad / s * ( ω =10) (Pa sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v). Log{η * ( ω =0.01)} / Log{η* ( ω =10)}≦0.0753×{apparent iodine value derived from non-conjugated polyene [A3]}+1.42 … Formula (v) Here, the complex viscosity η * ( ω =0.01) and the complex viscosity η * ( ω =10) is the complex viscosity η in requirement (6) * ( ω =0.1) and the complex viscosity η * ( ω =100) The same procedure is used to calculate the value of the frequency of the measurement.

[0044] The apparent iodine value derived from the non-conjugated polyene [A3] can be calculated by the following formula: Apparent iodine value derived from [A3] = weight fraction of [A3] × 253.81 / molecular weight of [A3]

[0045] In the formula (v), the left side represents the shear rate dependency which is an index of the amount of long chain branches, and the right side represents an index of the content of the non-conjugated polyene [A3] that is not consumed as long chain branches during polymerization. When the requirement (7) and the formula (v) are satisfied, the degree of long chain branches is not too high, which is preferable. On the other hand, when the formula (v) is not satisfied, it indicates that a large proportion of the copolymerized non-conjugated polyene [A3] is consumed in the formation of long chain branches.

[0046] Requirement (8) The copolymer (A) used in the present invention has a glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) of −65° C. or lower, and preferably −70° C. or lower. By using the copolymer (A) having a glass transition temperature within the above range, the low-temperature properties of the obtained transmission belt become good.

[0047] The copolymer (A) according to the present invention has a Mooney viscosity at 100°C of preferably 5-150, more preferably 5-100, further preferably 5-50, and particularly preferably 20-40.

[0048] When the Mooney viscosity ML(1+4)100°C is within the above range, the copolymer (A) has excellent roll processability even in a high hardness oil-less compound, and exhibits good post-treatment (ribbon handling properties) and excellent rubber physical properties.

[0049] <Method for producing copolymer (A)> The copolymer (A) according to the present invention can be obtained by various known production methods, for example, a conventionally known production method using a metallocene catalyst. For example, the metallocene catalyst and the production method using the catalyst can be adopted from the examples described in WO2015 / 122415, particularly paragraphs

[0249] to

[0320] of the publication.

[0050] <Carbon black (B)> Carbon black (B) is a component that contributes to improving, for example, the mechanical strength, modulus, and abrasion resistance of the resulting (crosslinked) molded article.

[0051] Examples of carbon black (B) include SRF, GPF, FEF, MAF, HAF, ISAF, SAF, FT, and MT. The surface of the carbon black may be treated with a silane coupling agent. Examples of commercially available carbon black include "Asahi #55G", "Asahi #50HG", "Asahi #60G", "Asahi #60UG", and "Asahi #70" (trade names, manufactured by Asahi Carbon Co., Ltd.), "Seest V", and "Seest SO" (trade names, manufactured by Tokai Carbon Co., Ltd.).

[0052] The composition of the present invention may contain one type of carbon black (B) or may contain two or more types of carbon black (B). The content of carbon black (B) in the composition of the present invention is usually 0.1 to 200 parts by mass, preferably 10 to 200 parts by mass, more preferably 20 to 100 parts by mass, and further preferably 30 to 50 parts by mass, relative to 100 parts by mass of component (A). Such an embodiment is preferable from the viewpoints of the mechanical strength of the obtained (crosslinked) molded article and the processability of the composition of the present invention.

[0053] <Short Fiber (C)> The composition of the present invention contains short fibers (C). By using the short fibers (C), the modulus and mechanical strength of the (crosslinked) molded article formed from the composition can be improved. Since the copolymer (A) has excellent kneadability with the short fibers (C), the composition of the present invention tends to have excellent moldability.

[0054] Examples of the short fibers (C) include fibers made of synthetic resins such as polyamide, polyimide, polyester, polyvinyl alcohol, rayon, polyolefin, polyarylate, polyphenylene sulfide, polyether ether ketone, polyparaphenylene benzobisoxazole, and fluorine-based polymers; and natural fibers such as cotton and wood cellulose fibers. Among these, short fibers made of synthetic resins are preferred, and short fibers made of polyamide are more preferred. The short fibers (C) are usually not short fibers formed from the copolymer (A).

[0055] Examples of polyamides include aliphatic polyamides such as polycapramide, poly-ω-aminoheptanoic acid, poly-ω-aminononanoic acid, polyundecaneamide, polyethylenediamineadipamide, polytetramethyleneadipamide, polyhexamethyleneadipamide, polyhexamethylenesebacamide, polyhexamethylenedodecamamide, polyoctamethyleneadipamide, and polydecamethyleneadipamide; polyparaphenylene Examples of such aromatic polyamides (aramid fibers) include terephthalamide (trade name "Kevlar (registered trademark)", manufactured by DuPont-Toray Co., Ltd.), polymetaphenylene isophthalamide, copolyparaphenylene-3,4'-oxydiphenylene terephthalamide, polymetaxylylene adipamide, polymetaxylylene pimelamide, polymetaxylylene azelamide, polyparaxylylene azelamide, and polyparaxylylene decanamide.

[0056] As the short fibers (C), from the viewpoint of further improving the tensile stress and tear strength of the resulting (crosslinked) molded body, short fibers made of aromatic polyamide, i.e., aramid short fibers, are preferred, and polyparaphenylene terephthalamide short fibers, polymetaphenylene isophthalamide short fibers, and copolyparaphenylene-3,4'-oxydiphenylene terephthalamide short fibers are more preferred.

[0057] The average fiber length of the short fibers (C) is usually 0.1 to 50 mm, preferably 0.5 to 10 mm, more preferably 0.5 to 6 mm, further preferably 1.0 to 5.0 mm, and particularly preferably 2.0 to 4.0 mm. The fiber diameter of the short fibers (C) is usually 0.1 to 100 μm, preferably 0.1 to 25 μm, and more preferably 1 to 20 μm.

[0058] The average fiber length of the staple fibers (C) can be determined, for example, by photographing the staple fibers with an optical microscope, measuring the lengths of 100 staple fibers randomly selected from the photograph, and calculating the arithmetic average.

[0059] The staple fibers (C) may be chopped fiber (cut fiber)-like staple fibers or pulp-like staple fibers having fibrils.

[0060] The composition of the present invention may contain one type of short fiber (C) or may contain two or more types of short fibers (C). The content of the short fibers (C) in the composition of the present invention is usually 0.1 to 100 parts by mass, preferably 0.1 to 30 parts by mass, more preferably 3 to 20 parts by mass, and further preferably 5 to 10 parts by mass, based on 100 parts by mass of the copolymer (A). Such an embodiment is preferable from the viewpoints of the modulus and mechanical strength of the (crosslinked) molded article obtained.

[0061] <Other ingredients> The composition of the present invention may further contain at least one selected from the group consisting of a crosslinking agent (D), a processing aid (E), a crosslinking aid (F), a surfactant, a softener, an inorganic filler, a reinforcing agent, an antioxidant, an activator, a moisture absorbent, an antistatic agent, a colorant, a lubricant, a thickener, trans-polyoctenylene, a modified polybutadiene, and a polymer other than component (A). Each of the components described below may be used alone or in combination of two or more kinds.

[0062] <Crosslinking agent (D)> The crosslinking agent (D) may be any crosslinking agent commonly used for crosslinking rubber, such as organic peroxides, sulfur compounds, phenolic resins, hydrosilicone compounds, amino resins, quinones or their derivatives, amine compounds, azo compounds, epoxy compounds, and isocyanate compounds. Among these, organic peroxides and sulfur compounds are preferred.

[0063] Examples of organic peroxides include dicumyl peroxide (DCP), di-tert-butyl peroxide, 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butyl peroxybenzoate, ert-butylperoxyisopropyl carbonate, diacetyl peroxide, lauroyl peroxide, and tert-butylcumyl peroxide.

[0064] In the composition of the present invention, when an organic peroxide is used as the crosslinking agent (D), the content of the organic peroxide is usually 0.1 to 20 parts by mass, preferably 0.2 to 15 parts by mass, and more preferably 0.5 to 10 parts by mass, per 100 parts by mass of the total of component (A) and other polymers (rubber, etc.) that require crosslinking and are blended as necessary.

[0065] When an organic peroxide is used as the crosslinking agent (D), it is preferable to use a crosslinking auxiliary (F) in combination. In this case, the composition of the present invention further containing the crosslinking auxiliary (F) may be used, and the organic peroxide may be blended into the composition before the crosslinking step, and the crosslinking step may be carried out.

[0066] Examples of the crosslinking aid (F) include sulfur; quinone dioxime-based crosslinking aids such as p-quinone dioxime; acrylic crosslinking aids such as ethylene glycol dimethacrylate (e.g., "Sunester EG" (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)) and trimethylolpropane trimethacrylate; allyl crosslinking aids such as diallyl phthalate and triallyl isocyanurate; maleimide-based crosslinking aids such as N,N'-m-phenylenedimaleimide (e.g., "Bulnoc PM" (trade name; manufactured by Ouchi Shinko Chemical Industry Co., Ltd.); divinylbenzene; and metal oxides such as zinc oxide (e.g., ZnO#1 / zinc oxide type 2 (JIS standard (K-1410)), manufactured by Hakusui Tech Co., Ltd.), magnesium oxide, and activated zinc oxide (e.g., zinc oxide such as "META-Z102" (trade name; manufactured by Inoue Lime Industry Co., Ltd.)). Zinc oxide is preferred.

[0067] When the composition of the present invention contains a crosslinking auxiliary (F), the content of the crosslinking auxiliary (F) is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, further preferably 2 to 10 parts by mass, and particularly preferably 2 to 7 parts by mass, relative to 100 parts by mass of the copolymer (A).

[0068] When a sulfur-based compound is used as the crosslinking agent (D), specific examples thereof include sulfur, sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, tetramethylthiuram disulfide, and selenium dithiocarbamate.

[0069] In the composition of the present invention, when a sulfur-based compound is used as the crosslinking agent (D), the content of the sulfur-based compound is usually 0.1 to 10 parts by mass, preferably 0.2 to 7.0 parts by mass, and more preferably 0.3 to 5.0 parts by mass, per 100 parts by mass of the total of component (A) and other polymers (rubbers, etc.) that require crosslinking and are blended as necessary.

[0070] When a sulfur-based compound is used as the crosslinking agent (D), it is preferable to use a vulcanization accelerator in combination. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, N-oxydiethylene-2-benzothiazole sulfenamide, N,N'-diisopropyl-2-benzothiazole sulfenamide, 2-mercaptobenzothiazole, 2-(4-morpholinodithio)benzothiazole, 2-(2,4-dinitrophenyl)mercaptobenzothiazole, 2-(2,6-diethyl-4-morpholinothio)benzothiazole, and dibenzothiazyl disulfide; guanidine-based vulcanization accelerators such as diphenylguanidine, triphenylguanidine, and diorthotolylguanidine; aldehyde amine-based vulcanization accelerators such as acetaldehyde-aniline condensation product and butylaldehyde-aniline condensation product; 2-mercaptoimidazoline; thiourea-based vulcanization accelerators such as diethylthiourea and dibutylthiourea; thiuram-based vulcanization accelerators such as tetramethylthiuram monosulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrabutylthiuram disulfide, and dipentamethylenethiuram tetrasulfide; dithioacid salt-based vulcanization accelerators such as zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, and tellurium diethyldithiocarbamate; thiourea-based vulcanization accelerators such as ethylenethiourea (for example, Suncerer 22C (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), N,N'-diethylthiourea, and N,N'-dibutylthiourea; xanthate-based vulcanization accelerators such as zinc dibutylxatogenate; and others such as zinc oxide.

[0071] When the composition of the present invention contains a vulcanization accelerator, the content of the vulcanization accelerator is usually 0.1 to 20 parts by mass, preferably 0.2 to 15 parts by mass, and more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass in total of component (A) and other polymers (rubber, etc.) that require crosslinking and are blended as necessary.

[0072] The vulcanization aid can be preferably used when the crosslinking agent (D) is a sulfur-based compound, and examples thereof include zinc oxide (e.g., ZnO#1 / zinc oxide type 2, manufactured by Hakusui Tech Co., Ltd.), magnesium oxide, and zinc oxide (e.g., zinc oxide such as "META-Z102" (trade name; manufactured by Inoue Lime Industry Co., Ltd.)).

[0073] When the composition of the present invention contains a vulcanization aid, the content of the vulcanization aid is usually 1 to 20 parts by mass, preferably 2 to 10 parts by mass, and more preferably 3 to 8 parts by mass, per 100 parts by mass of the total of component (A) and other polymers (rubber, etc.) that require crosslinking and are blended as necessary.

[0074] <Processing aids (E)> As the processing aid (E), a wide variety of processing aids that are generally compounded with rubber can be used. Examples of processing aids (E) include ricinoleic acid, stearic acid, palmitic acid, lauric acid, barium stearate, zinc stearate, calcium stearate, and esters. Among these, stearic acid is preferred.

[0075] When the composition of the present invention contains a processing aid (E), the content of the processing aid (E) is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 5.0 parts by mass, even more preferably 0.5 to 3.0 parts by mass, and particularly preferably 0.7 to 2.0 parts by mass, per 100 parts by mass of component (A).

[0076] <Surfactant> Examples of the surfactant include a nonionic surfactant, a cationic surfactant, an anionic surfactant, and an amphoteric surfactant.

[0077] Examples of nonionic surfactants include polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene higher alcohol ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene alkyl ether, polyoxyethylene myristyl ether, polyoxyethylene octyldodecyl ether, polyoxyethylene alkylene alkyl ether, polyoxyethylene distyrenated phenyl ether, polyoxyethylene derivatives, polyoxyethylene polyoxypropylene glycol, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearyl ether, polyoxyethylene sorbitan monostearate ... sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tetraoleate, glycerol monostearate, glycerol monooleate, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan distearate, sorbitan tristearate, sorbitan monooleate, sorbitan trioleate, sorbitan sesquioleate, polyethylene glycol monolaurate, polyethylene glycol monostearate, polyethylene glycol distearate, polyethylene glycol monooleate, polyoxyethylene hydrogenated castor oil, polyoxyethylene alkylamines, and alkyl alkanolamides.

[0078] Examples of cationic surfactants include coconut amine acetate, stearyl amine acetate, lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, cetyl trimethyl ammonium chloride, distearyl dimethyl ammonium chloride, dihydrogenated tallow alkyl dimethyl ammonium chloride, alkyl benzyl dimethyl ammonium chloride, bishydroxyethyl alkyl (C8-18) methyl ammonium chloride, bis (polyoxyethylene) alkyl (C8-18) methyl ammonium chloride, and bishydroxyethyl oleyl methyl ammonium chloride. Examples of commercially available cationic surfactants include Lipocard (registered trademark) (e.g., Lipocard 2HT flakes), Liposocard (registered trademark) (both manufactured by Lion Specialty Chemicals Co., Ltd.).

[0079] Examples of anionic surfactants include mixed fatty acid soda soap, semi-hardened beef tallow fatty acid soda soap, sodium stearate soap, semi-hardened beef tallow fatty acid potassium soap, potassium oleate soap, castor oil potassium soap, sodium lauryl sulfate, sodium higher alcohol sulfate, triethanolamine lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium alkylnaphthalenesulfonate, sodium dialkylsulfosuccinate, sodium alkyldiphenyletherdisulfonate, potassium alkylphosphate, sodium polyoxyethylene lauryl ether sulfate, sodium polyoxyethylene alkyl ether sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate, sodium alkane sulfonate, and the sodium salt of β-naphthalenesulfonic acid formalin condensate.

[0080] Examples of amphoteric surfactants include lauryl betaine, stearyl betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, and lauryl dimethylamine oxide. The surfactant is preferably at least one selected from the group consisting of cationic surfactants and anionic surfactants, and more preferably a cationic surfactant.

[0081] In the composition of the present invention, the content of the surfactant is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of component (A).

[0082] <Softener> Examples of softeners include petroleum-based softeners such as process oil, lubricating oil, paraffin oil, liquid paraffin, petroleum asphalt, and Vaseline; coal tar-based softeners such as coal tar; fatty oil-based softeners such as castor oil, linseed oil, rapeseed oil, soybean oil, and coconut oil; waxes such as beeswax and carnauba wax; fatty acids or salts thereof such as ricinoleic acid, palmitic acid, barium stearate, and calcium stearate; naphthenic acid, pine oil, rosin, and derivatives thereof; synthetic polymeric substances such as terpene resins, petroleum resins, and coumarone-indene resins; ester-based softeners such as dioctyl phthalate and dioctyl adipate; and other microcrystalline waxes, liquid polybutadiene, modified liquid polybutadiene, hydrocarbon-based synthetic lubricating oils, tall oil, and sub(factice). Petroleum-based softeners are preferred, and process oil is more preferred.

[0083] When the composition of the present invention contains a softener, the content of the softener is usually 2 to 100 parts by mass, preferably 5 to 100 parts by mass, more preferably 5 to 30 parts by mass, and even more preferably 10 to 20 parts by mass, per 100 parts by mass of the total of component (A) and other polymers (elastomers, rubbers, etc.) that are blended as necessary.

[0084] <Inorganic fillers> Examples of inorganic fillers include light calcium carbonate, heavy calcium carbonate, talc, and clay. Of these, heavy calcium carbonate is preferred.

[0085] When the composition of the present invention contains an inorganic filler, the content of the inorganic filler is usually 2 to 50 parts by mass, and preferably 5 to 50 parts by mass, per 100 parts by mass of the total of component (A) and other polymers (elastomers, rubbers, etc.) that are blended as necessary.

[0086] <Reinforcing agent> Examples of reinforcing agents include silica, calcium carbonate, activated calcium carbonate, fine talc, and differential silicic acid, except for the above-mentioned carbon black (B) and inorganic fillers. Among these, silica is preferred.

[0087] When the composition of the present invention contains a reinforcing agent, the content of the reinforcing agent is usually 0.1 to 100 parts by mass, preferably 5 to 30 parts by mass, more preferably 6 to 20 parts by mass, and even more preferably 7 to 15 parts by mass, relative to 100 parts by mass in total of component (A) and other polymers (elastomers, rubbers, etc.) that are blended as necessary.

[0088] <Anti-aging agent (stabilizer)> The composition of the present invention can extend the life of a (crosslinked) molded article formed from the composition by containing an antioxidant (stabilizer). Examples of the antioxidant include amine-based antioxidants, phenol-based antioxidants, and sulfur-based antioxidants.

[0089] Examples of the amine-based antiaging agents include aromatic secondary amine-based antiaging agents such as phenylbutylamine, N,N-di-2-naphthyl-p-phenylenediamine, etc. Examples of the phenol-based antiaging agents include dibutylhydroxytoluene, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (e.g., "Irganox 1010" (trade name; manufactured by BASF)). Examples of sulfur-based anti-aging agents include thioether-based anti-aging agents such as bis[2-methyl-4-(3-n-alkylthiopropionyloxy)-5-t-butylphenyl]sulfide; dithiocarbamate-based anti-aging agents such as nickel dibutyldithiocarbamate; 2-mercaptobenzoylimidazole, 2-mercaptobenzimidazole (for example, "Sandant MB" (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), zinc salt of 2-mercaptobenzimidazole, dilaurylthiodipropionate, and distearylthiodipropionate.

[0090] When the composition of the present invention contains an antioxidant, the content of the antioxidant is usually 0.3 to 10 parts by mass, and preferably 0.5 to 7.0 parts by mass, per 100 parts by mass of the total of component (A) and other polymers (elastomers, rubbers, etc.) that are blended as necessary.

[0091] <Activator> Examples of the activator include amines such as di-n-butylamine, dicyclohexylamine, and monoethanolamine; activators such as diethylene glycol, polyethylene glycol, lecithin, triaryl methylate, and zinc compounds of aliphatic or aromatic carboxylic acids; zinc peroxide preparations; octadecyltrimethylammonium bromide, synthetic hydrotalcite, and special quaternary ammonium compounds.

[0092] When the composition of the present invention contains an activator, the content of the activator is usually 0.2 to 10 parts by mass, and preferably 0.3 to 5 parts by mass, per 100 parts by mass of the total of component (A) and other polymers (elastomers, rubbers, etc.) that are blended as necessary.

[0093] <Moisture absorbent> Examples of moisture absorbents include calcium oxide, silica gel, sodium sulfate, molecular sieves, zeolite, and white carbon. When the composition of the present invention contains a moisture absorbent, the content of the moisture absorbent is usually 0.5 to 15 parts by mass, and preferably 1.0 to 12 parts by mass, per 100 parts by mass of the total of component (A) and other polymers (elastomers, rubbers, etc.) that are blended as necessary.

[0094] <Trans-polyoctenylene> Trans polyoctenylene is a polymer of octenylene having a trans structure, and is mainly a metathesis polymer of cyclooctene having a trans double bond. Here, cyclooctene can be obtained by dimerizing 1,3-butadiene to obtain cycloocta-1,5-diene, and then hydrogenating the cycloocta-1,5-diene. The composition of the present invention contains trans-polyoctenylene, and thus has an excellent balance between modulus and elongation, and can improve abrasion resistance. The trans-polyoctenylene (M) according to the present invention is manufactured and sold by Evonik Industries under the trade name VESTENAMER®.

[0095] When the composition of the present invention contains trans-polyoctenylene, the composition of the present invention contains preferably 0.5 to 50 parts by mass, more preferably 1 to 30 parts by mass, still more preferably 2 to 10 parts by mass, and particularly preferably 3 to 8 parts by mass of trans-polyoctenylene per 100 parts by mass of the total of component (A) and other polymers (elastomers, rubbers, etc.) blended as necessary. When the blending amount of trans-polyoctenylene in the present composition is within the above range, the composition has excellent mechanical strength and abrasion resistance.

[0096] <Modified polybutadiene> The modified polybutadiene is a polybutadiene modified with an unsaturated carboxylic acid and / or its derivatives.

[0097] The composition of the present invention contains modified polybutadiene, and thus has excellent heat aging resistance and improved abrasion resistance.

[0098] Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, α-ethylacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, methyltetrahydrophthalic acid, and endo-cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid (Nadic Acid (trademark)). Derivatives of these include acid halides, amides, imides, acid anhydrides, and esters. Among these, unsaturated dicarboxylic acids and their acid anhydrides are preferred, maleic acid and maleic anhydride are more preferred, and maleic anhydride is particularly preferred.

[0099] Modified polybutadienes include maleic anhydride modified polybutadienes manufactured and sold by Cray Valley under trade names such as Ricon 130MA8, Ricon 130MA13, Ricon 130MA20, Ricon 131MA5, Ricon 131MA10, Ricon 131MA17, Ricon 131MA18, Ricon 131MA20, and Ricon 184MA6.

[0100] When the composition of the present invention contains modified polybutadiene, the composition contains the modified polybutadiene in an amount of preferably 0.5 to 50 parts by mass, more preferably 0.5 to 30 parts by mass, still more preferably 0.5 to 10 parts by mass, and particularly preferably 0.5 to 5 parts by mass, per 100 parts by mass of the total of component (A) and other polymers (elastomers, rubbers, etc.) blended as necessary. When the blending amount of modified polybutadiene in the composition is within the above range, the composition has excellent mechanical strength and abrasion resistance.

[0101] <Other polymers> The composition of the present invention may further contain other polymers than component (A), such as rubbers and / or elastomers. Other polymers that require crosslinking include, for example, rubbers such as natural rubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, butyl rubber, acrylic rubber, silicone rubber, fluororubber, and urethane rubber.

[0102] Other polymers that do not require crosslinking include, for example, elastomers such as styrene-butadiene block copolymers (SBS), styrene-based thermoplastic elastomers (TPS) such as polystyrene-poly(ethylene-butylene)-polystyrene (SEBS) and polystyrene-poly(ethylene-propylene)-polystyrene (SEPS), olefin-based thermoplastic elastomers (TPO), vinyl chloride-based elastomers (TPVC), ester-based thermoplastic elastomers (TPC), amide-based thermoplastic elastomers (TPA), urethane-based thermoplastic elastomers (TPU), and other thermoplastic elastomers (TPZ). When the composition of the present invention contains another polymer, the content of the other polymer is usually 100 parts by mass or less, and preferably 80 parts by mass or less, per 100 parts by mass of component (A).

[0103] <Preparation of Composition> The composition of the present invention can be prepared by kneading component (A), carbon black (B), short fibers (C), and other components at a desired temperature using a kneading machine such as a mixer, kneader, or roll.

[0104] One embodiment of the composition of the present invention is prepared, for example, as follows. Component (A), carbon black (B), short fiber (C), and other predetermined components are put into a kneader and kneaded and homogenized under predetermined heating conditions (e.g., 80 to 200°C for 3 to 30 minutes) (kneading A). In kneading A, a crosslinking agent or the like that crosslinks component (A) when heated to the heating temperature of kneading A is not added. The temperature of the mixture kneaded in kneading A is then lowered to below the crosslinking temperature of the crosslinking agent (e.g., 130°C or lower), and the crosslinking agent or the like that was not added in kneading A is added to the mixture, and the mixture is further kneaded and homogenized under predetermined heating conditions (e.g., roll temperature 30 to 80°C for 1 to 30 minutes) (kneading B), to obtain the composition of the present invention.

[0105] The composition of the present invention, in the composition (mixture A) before blending with the crosslinking agent, has a Mooney viscosity ML(1+4) at 125°C of usually 10 to 250, preferably 10 to 100, and more preferably 10 to 50. A composition having a Mooney viscosity within the above range exhibits good post-treatment quality and has excellent rubber properties.

[0106] [(Crosslinked) molded body, power transmission belt] A (crosslinked) molded article can be obtained from the composition of the present invention. The composition of the present invention can be molded by a thermoforming method such as extrusion molding, injection molding, press molding, calendar molding, transfer molding, and foam molding. In the present invention, the crosslinking temperature of the composition is usually 140° C. or higher, preferably 150 to 220° C., and more preferably 160 to 200° C. In addition, this crosslinking reaction can be carried out in air.

[0107] In the present invention, the (crosslinked) molded product can be suitably used as a component of a transmission belt. For example, the composition of the present invention has high adhesive strength suitable for molding processability and is excellent in belt processability. In addition, by using the composition of the present invention, a component of a transmission belt having high rubber elasticity, abrasion resistance, heat resistance, and cold resistance can be manufactured.

[0108] The power transmission belt of the present invention has a (crosslinked) molded article formed from the composition of the present invention. Examples of the transmission belt of the present invention include friction transmission belts such as V-belts and V-ribbed belts, and meshing transmission belts such as timing belts. Examples of the transmission belt include automobile transmission belts, motorcycle transmission belts, and general industrial machine transmission belts. Examples of the V-belt include wrapped belts and raw edge belts.

[0109] One embodiment of the transmission belt may have, for example, an adhesive rubber part in which a core wire is embedded, and may further have a bottom rubber part formed on the lower surface of the adhesive rubber part. The transmission belt may have an upper canvas formed on the adhesive rubber part and / or a lower canvas formed under the bottom rubber part, as necessary. The composition of the present invention is preferably used to form, for example, the adhesive rubber part and / or the bottom rubber part. Specifically, a cross-linked molded part formed from the composition of the present invention is preferably used as the adhesive rubber part and / or the bottom rubber part.

[0110] The core wire, which is a tensile member of the power transmission belt, extends in the longitudinal direction of the belt in the bonded rubber section. An example of the core wire is a polyester cord. The bonded rubber section surrounds the core wire and is bonded to the core wire. In one embodiment, for example, the composition of the present invention is disposed around the core wire and crosslinked to form the bonded rubber section bonded to the core wire. Examples of the canvas include canvas made of cotton, a blend of cotton and polyester, and a blend of cotton and polyamide. EXAMPLES

[0111] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0112] <Physical properties of ethylene-α-olefin-non-conjugated polyene copolymer> [Molar amounts of structural units derived from ethylene, structural units derived from α-olefins, and structural units derived from non-conjugated polyenes] The molar amount is 1 The intensity was measured using a H-NMR spectrometer. Details of the measurement conditions are described in WO 2015 / 122415.

[0113] [Weight fraction of structural units derived from ethylene and structural units derived from non-conjugated polyenes] The weight fraction is 13 The measured values ​​were obtained by C-NMR. The measured values ​​were obtained by using an ECX400P nuclear magnetic resonance apparatus (manufactured by JEOL Ltd.) at a measurement temperature of 120°C, a measurement solvent of orthodichlorobenzene / deuterated benzene = 4 / 1, and an accumulation number of 8000 times. 13 The results were obtained by measuring the C-NMR spectrum.

[0114] [Iodine value] The apparent iodine value derived from the non-conjugated polyene [A3] (hereinafter also referred to as the “[A3] iodine value”) is calculated by the following formula: [A3] iodine value = weight fraction of [A3] × 253.81 / molecular weight of [A3]

[0115] [Mooney Viscosity] The Mooney viscosity (ML(1+4) 100° C., 125° C.) was measured using a Mooney viscometer (Shimadzu Corporation, SMV202 type) in accordance with JIS K6300 (1994).

[0116] [B value] The measurement solvent was o-dichlorobenzene-d4 / benzene-d6 (4 / 1 [v / v]) at a measurement temperature of 120°C. 13 A C-NMR spectrum (100 MHz, JEOL ECX400P) was measured, and calculation was performed based on the following formula (i). B value=([EX]+2[Y]) / [2×[E]×([X]+[Y])]···(i) Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins having 4 to 20 carbon atoms [A2] and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins having 4 to 20 carbon atoms [A2] dyad chain fraction.

[0117] [Number of branch points BrNo] The absolute molecular weight distribution was measured using a 3D-high temperature GPC device PL-GPC220 (Polymer Laboratories), and the intrinsic viscosity was measured using a viscometer. The main measurement conditions were as follows: Detector: Differential refractometer / GPC device built-in 2-angle light scattering photometer PD2040 type (manufactured by Precison Detectors) Bridge type viscometer PL-BV400 (Polymer Laboratories) Column: TSKgel GMHHR-H(S)HT x 2 + TSKgel+GMHHR-M(S) x 1 (each with inner diameter of 7.8 mm and length of 300 mm) Temperature: 140℃ Mobile phase: 1,2,4-trichlorobenzene (containing 0.025% BHT) Injection volume: 0.5mL Sample concentration: ca 1.0mg / mL Sample filtration: Filtration through a sintered filter with a pore size of 1.0 μm The dn / dc value required to determine the absolute molecular weight was determined for each sample from the dn / dc value of standard polystyrene (molecular weight 190,000), 0.053, and the response intensity of the differential refractometer per unit injected mass. The long chain branching parameter g' for each eluted component was calculated from the relationship between the intrinsic viscosity obtained from the viscometer and the absolute molecular weight obtained from the light scattering photometer. i was calculated from equation (v-1).

[0118]

number

[0119] Here, [η] = KM vThe equation was applied: v = 0.725. This equation is called the Mark-Houwink-Sakurada equation, where K is the solvent constant and M is the average molecular weight. Further, the average values ​​of g' were calculated from the following formulas (v-2), (v-3), and (v-4). Note that a trendline assuming the presence of only short chain branches was determined for each sample.

[0120]

number

[0121] Furthermore, g' w The number of branching points per molecular chain, BrNo, was calculated using the Zimm-Stockmayer formula (v-5). g is the long chain branching parameter calculated from the radius of gyration Rg, and the following simple correlation is made between g' calculated from the intrinsic viscosity. g=g' (1 / ε) (ε(structure factor)=0.5~1.5) Various values ​​have been proposed for ε in the formula depending on the shape of the molecule. Here, the calculation was performed assuming ε = 1 (i.e. g' = g).

[0122]

number

[0123] [Intrinsic viscosity [η]] The intrinsic viscosity [η] (dl / g) of the copolymer was measured using a fully automatic intrinsic viscometer manufactured by Rigo Co., Ltd. at a temperature of 135° C. and in decalin as a measurement solvent.

[0124] [Weight average molecular weight (Mw)] The weight average molecular weight (Mw) of the copolymer was determined using a 3D-high temperature GPC apparatus (PL-GPC220, manufactured by Polymer Laboratories) under the same measurement conditions as those for the number of branch points BrNo.

[0125] [Complex viscosity η * and P value] The rheometer used was the Ares viscoelasticity measuring device (manufactured by Rheometric Scientific), and the complex viscosity η at a frequency of ω = 0.01 rad / s was measured under the conditions of 190°C and 1.0% strain. * ( ω =0.01) , complex viscosity η at frequency ω=0.1rad / s * ( ω =0.1) , complex viscosity η at frequency ω=10rad / s * ( ω =10) and the complex viscosity η at frequency ω = 100 rad / s * ( ω =100) (All units are Pa·sec.)

[0126] In addition, the obtained results show that η * ( ω =0.1) and η * ( ω =100) The ratio of complex viscosity to * The P-value (η * ( ω =0.1) / η * ( ω =100) ) was calculated.

[0127] [Glass transition temperature (Tg)] The glass transition temperature (Tg) of the copolymer was determined by DSC measurement under the following conditions. Using a differential scanning calorimeter (RDC220, manufactured by SII), approximately 10 mg of a sample was heated from 30°C to 200°C at a heating rate of 50°C / min in a nitrogen atmosphere and held at that temperature for 10 minutes. It was then cooled to -100°C at a heating rate of 10°C / min, held at that temperature for 5 minutes, and then heated to 200°C at a heating rate of 10°C / min.

[0128] The glass transition temperature (Tg) is detected as the DSC curve bending due to the change in specific heat during the second heating, and the baseline shifts in parallel. The glass transition temperature (Tg) is determined as the temperature at the intersection of the tangent to the baseline lower than this bending and the tangent to the point where the slope of the bending part is maximum.

[0129] [Ethylene-α-olefin-non-conjugated polyene copolymer] In the following examples, copolymers (A-1) and (a-1) to (a-3) obtained in the following Production Examples 1 to 4 were used as copolymers.

[0130] <Production Example 1> A polymerization reaction of ethylene, 1-butene, and 5-vinyl-2-norbornene (VNB) was continuously carried out at 95°C using a 300 L volume polymerization vessel equipped with an agitator. Hexane (feed rate: 30.5 L / h) was used as the polymerization solvent and was continuously fed to the polymerization reactor so that the ethylene feed rate was 5.3 kg / h, the 1-butene feed rate was 21.5 kg / h, the VNB feed rate was 566 g / h, and the hydrogen feed rate was 10 NL / h.

[0131] While maintaining the polymerization pressure at 1.6 MPaG and the polymerization temperature at 95°C, di(p-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride was used as the main catalyst and continuously fed to the polymerization reactor at a feed rate of 0.00903 mmol / h. In addition, (C6H5)3CB(C6F5)4 was continuously fed to the polymerization reactor at a feed rate of 0.045 mmol / h as a cocatalyst, and triisobutylaluminum (TIBA) was continuously fed to the polymerization reactor at a feed rate of 30 mmol / h as an organoaluminum compound.

[0132] In this way, a solution containing 20% ​​by mass of ethylene-1-butene-VNB copolymer formed from ethylene, 1-butene and VNB was obtained. A small amount of methanol was added to the polymerization reaction liquid withdrawn from the bottom of the polymerization vessel to terminate the polymerization reaction, and the ethylene-1-butene-VNB copolymer was separated from the solvent by steam stripping and then dried under reduced pressure at 80°C for a whole day and night.

[0133] By the above operations, ethylene-1-butene-VNB copolymer (A-1) was obtained at a rate of 8.5 kg per hour. The physical properties of the obtained copolymer (A-1) were measured by the methods described above. The results are shown in Table 1.

[0134] <Production Example 2> According to the description of [Synthesis Example C1] of WO 2015 / 122415, an ethylene-1-butene-5-ethylidene-2-norbornene (ENB) copolymer (a-1) having the following physical properties was obtained. The physical properties of the obtained copolymer (a-1) were measured by the method described above. The results are shown in Table 1.

[0135] <Production Example 3> A 300 L polymerization vessel equipped with an agitator was continuously fed with 58.3 L / h of dehydrated and purified hexane solvent, 4.5 mmol / h of triisobutylaluminum (TiBA), 0.150 mmol / h of (C6H5)3CB(C6F5)4, and 0.030 mmol / h of di(p-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride.

[0136] At the same time, ethylene was continuously fed into the polymerization reactor at a feed rate of 6.6 kg / h, propylene at a feed rate of 9.3 kg / h, VNB at a feed rate of 340 g / h and hydrogen at a feed rate of 18 L / h, and copolymerization was carried out under the conditions of a polymerization temperature of 87°C, a polymerization pressure of 1.6 MPaG and a residence time of 1 hour.

[0137] The solution of ethylene-propylene-VNB copolymer (a-2) produced in the polymerization reactor was continuously discharged at a flow rate of 88.0 L / h, heated to 170°C (pressure increased to 4.1 MPaG), and fed to a phase separator. At this time, ethanol, a polymerization inhibitor, was continuously fed to the discharge line in an amount of 0.1 mol times the amount of TiBA in the liquid component extracted from the polymerization reactor.

[0138] In the phase separator, the ethylene-propylene-VNB copolymer (a-2) solution was separated into a dense phase (lower phase) containing a large amount of ethylene-propylene-VNB copolymer (a-2) and a dilute phase (upper phase) containing a small amount of ethylene-propylene-VNB copolymer (a-2). The separated thick phase was introduced into the heat exchanger at 85.4 L / h and then into the hopper. The solvent contained in the thick phase was evaporated and separated, and ethylene-propylene-VNB copolymer (a-2) was obtained at a rate of 7.8 kg / h.

[0139] The physical properties of the obtained copolymer (a-2) were measured by the method described above. The results are shown in Table 1. The molecular weight distribution obtained by 3D-GPC measurement of the obtained copolymer (a-2) showed two or more peaks, and the area of ​​the peak appearing on the side of the smallest molecular weight was 5% of the total peak area.

[0140] <Production Example 4> An ethylene-propylene-VNB copolymer (a-3) was produced in the same manner as in Production Example 3, except that the molecular weight of the resulting copolymer (a-3) was controlled by the amount of hydrogen fed. The physical properties of the resulting copolymer (a-3) were measured by the methods described above. The results are shown in Table 1.

[0141] [Table 1]

[0142] [Example 1] Using a MIXTRON BB MIXER (manufactured by Kobe Steel, Ltd., BB-2 type, volume 1.7 L, rotor 2WH), 100 parts by mass of copolymer (A-1) was mixed with 1 part by mass of stearic acid as a processing aid and ZnO#1 / zinc oxide type 2 (JIS Compound 1 was obtained by blending 5 parts by mass of ethylenediaminetetraacetate (Ethylenediaminetetraacetate), 2 parts by mass of Irganox 1010 (pentaerythritol tetrakis [3- (3,5-di-tert-butyl-4-hydroxyphenyl) propionate]) as an anti-aging agent, 4 parts by mass of Sandant MB (2-mercaptobenzimidazole) as an anti-aging agent, 40 parts by mass of Asahi #70 as carbon black, 10 parts by mass of Silica VN3 as silica, 15 parts by mass of Diana Process Oil PW-380 (paraffin-based process oil) as a softener, and 8 parts by mass of aramid short fiber (average fiber length 3.5 mm) as short fiber, and then kneading.

[0143] The kneading conditions for preparation of compound 1 were: rotor rotation speed 40 rpm, floating weight pressure 3 kg / cm 2 The kneading time was 5 minutes, and the kneading discharge temperature was 144°C.

[0144] Next, after confirming that the temperature of Compound 1 had reached 40°C, 6.8 parts by mass of DCP-40C (dicumyl peroxide 40% by mass) as a crosslinking agent and 2 parts by mass of Valnoc PM as a crosslinking aid were added to Compound 1 and kneaded using a 6-inch roll to obtain Compound 2.

[0145] The kneading conditions for preparing compound 2 were as follows: roll temperature: front roll / rear roll = 50°C / 50°C, roll peripheral speed: front roll / rear roll = 18 rpm / 15 rpm, roll gap: 3 mm, and kneading time: 8 minutes to obtain compound 2.

[0146] Compound 2 was pressed at 170° C. for 15 minutes using a press molding machine to produce a crosslinked sheet having a thickness of 2 mm. The crosslinked sheet thus obtained was subjected to the hardness test, tensile test, heat aging resistance test, and DIN abrasion test described below.

[0147] [Examples 2 to 4, Comparative Examples 1 to 3] The same procedure was followed as in Example 1, but based on the composition and cure system set out in Table 2.

[0148] [Adhesiveness (probe tack integral value)] Using a tack tester (TAC-II) manufactured by Rhesca Corporation, a load of 200 gf was applied to a stainless steel probe having a diameter of 5 mm for each of the compositions 2 in Examples 1 to 4 and Comparative Examples 1 to 3, and the peak value (gf) and the stress integral value (gf·sec) were measured when the probe was peeled off at a speed of 120 mm / min. This measurement was carried out 10 times at 23°C, and the average value of the integral value (probe tack integral value) was calculated as an index of adhesion. The same test was also carried out at 50°C, and the peak value (gf) and the average value of the integral value (probe tack integral value) were calculated.

[0149] [Roll processability] When Formulation 2 was prepared under the conditions and by the method described in Example 1, the state in which the composition was wound around the 6-inch roll was evaluated according to the following criteria. ×: The composition was not wound around the roll. ◯: The composition was wrapped around the roll and did not fall off from the edges.

[0150] [Hardness test (Durometer-A)] The flat portions of the crosslinked sheets each having a thickness of 2 mm were overlapped to form a sheet having a thickness of 12 mm, and the hardness (Duro-A) was measured in accordance with JIS K6253.

[0151] [Tensile test: modulus, tensile stress at break, tensile elongation at break] The crosslinked sheet was punched out to a thickness of 2 mm to prepare a No. 3 dumbbell test piece described in JIS K6251 (1993). Using this test piece, a tensile test was carried out according to the method specified in JIS K6251, paragraph 3, at a measurement temperature of 25°C and a tensile speed of 500 mm / min. The tensile stress when the elongation rate was 5% (5% modulus (M5)) and the tensile stress when the elongation rate was 10% (10% modulus (M 10)), tensile stress at break (T B ) and tensile elongation at break (E B ) was measured.

[0152] [Heat resistance test (heat aging resistance test)] The crosslinked sheet having a thickness of 2 mm was subjected to a heat aging test in accordance with JIS K6257 by holding the sheet at 170°C for 168 hours. The hardness of the sheet after the heat aging test, M5, M 10 , T B and E B was measured in the same manner as in the hardness test and tensile test.

[0153] [DIN abrasion test (DIN abrasion amount)] A disk-shaped test piece with a diameter of 16.0±0.2 mm and a thickness of 6 mm or more was prepared from the above crosslinked sheet with a thickness of 2 mm in accordance with JIS-K6264-2:2005. The test piece was subjected to a DIN abrasion test by rotating a drum with a diameter of 150.0±0.2 mm and a length of 500 mm at 40 revolutions per minute under a load of 1 kgf over an abrasion distance of 40.0±0.2 m, and the amount of abrasion (DIN abrasion amount: unit mm 3 ) was measured.

[0154] [Table 2]

[0155] The materials used in Table 2 were as follows: Chloroprene rubber: DCR-40 (manufactured by Denka) Processing aid: stearic acid (NOF Corporation) Vulcanization aid: ZnO#1, zinc oxide (Hakusui Tech Co., Ltd.), MgO#150 (Kyowa Chemical Industry Co., Ltd.) Anti-aging agent: Irganox 1010 (BASF), Sandant MB (manufactured by Sanshin Chemical Industry Co., Ltd.) Nocrac AD-F (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) Nocrac 6PPD (Ouchi Shinko Chemical Industry Co., Ltd.) Trans polyoctenylene: VESTENAMER® 8012 (manufactured by Evonik Industries) Maleic anhydride modified polybutadiene: Ricon 131MA17 (manufactured by Cray Valley) Carbon black: Asahi #70 (manufactured by Asahi Carbon Co., Ltd.), Asahi #55G: Carbon black (manufactured by Asahi Carbon Co., Ltd.) Hydrophilic silica: Silica VN3 (EVONIC) Aerosil 200 (EVONIC) Paraffin-based process oil: PW-380 (Idemitsu Kosan Co., Ltd.) Naphthenic process oil: AH-16 (Idemitsu Kosan) Short fibers: Kevlar (aramid short fibers) (manufactured by Toray DuPont) Crosslinking agent (organic peroxide): DCP-40C, cyclohexane peroxide (manufactured by Kayaku Akzo Co., Ltd.) Crosslinking agent: Barnoc PM (Ouchi Shinko Chemical Industry Co., Ltd.) Sunester EG (manufactured by Sanshin Chemical Industry Co., Ltd.) Vulcanization accelerator: Sancerer 22C (manufactured by Sanshin Chemical Industry Co., Ltd.)

Claims

1. The polymer has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in the molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfies the following requirements (1) to (4): the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms contains a structural unit derived from 1-butene, an ethylene / α-olefin / non-conjugated polyene copolymer (A), in which the structural unit derived from the non-conjugated polyene [A3] contains a structural unit derived from 5-vinyl-2-norbornene; Carbon black (B); and (C) short fibers. 【Chemistry 1】 Requirement (1): the molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms is 40 / 60 to 90 / 10; Requirement (2): the content of the structural units derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from ethylene [A1], the α-olefin [A2] having 4 to 20 carbon atoms, and the non-conjugated polyene [A3]; Requirement (3): The B value represented by the following formula (i) is 1.20 or more; B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2] and a non-conjugated polyene [A3], and [EX] represents the ethylene [A1]-α-olefin having 4 to 20 carbon atoms [A2] dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC, satisfies the following formula (ii): BrNo≧0.5...Formula (ii)

2. The composition for a transmission belt according to claim 1, wherein the ethylene / α-olefin / non-conjugated polyene copolymer (A) satisfies one or more of the following requirements (5) to (8): Requirement (5): the weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (wt%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii); 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 ... Formula (iii) Requirement (6): Complex viscosity η at a frequency ω = 0.1 rad / s obtained by linear viscoelasticity measurement (190 ° C.) using a rheometer * ( ω =0.1) (Pa sec) and the complex viscosity η at a frequency ω = 100 rad / s * ( ω =100) (Pa sec) P [η * ( ω =0.1) / * ( ω =100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of the [A3] satisfy the following formula (iv); P / ([η] 2.9 ) ≦ weight fraction of [A3] × 6 ... formula (iv) Requirement (7): Complex viscosity η at a frequency ω = 0.01 rad / s obtained by linear viscoelasticity measurement (190 ° C.) using a rheometer * ( ω =0.01) (Pa sec) and the complex viscosity η at a frequency ω = 10 rad / s * ( ω =10) (Pa·sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v). Log{η * ( ω =0.01) } / Log{η * ( ω =10) }≦0.0753×{apparent iodine value derived from the non-conjugated polyene [A3]}+1.42 ... formula (v) Requirement (8): The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is −65° C. or lower.

3. 2. The composition for a transmission belt according to claim 1, wherein the content of the short fibers (C) is 0.1 to 100 parts by mass based on 100 parts by mass of the copolymer (A).

4. 2. The composition for a transmission belt according to claim 1, wherein the short fibers (C) are aramid fibers.

5. 2. The composition for a transmission belt according to claim 1, wherein the copolymer (A) has a Mooney viscosity ML(1+4) 100° C. of 5 to 150.

6. The composition for a transmission belt according to claim 1, further comprising an organic peroxide as a crosslinking agent (D).

7. 2. The composition for a transmission belt according to claim 1, further comprising 0.1 to 20 parts by mass of a processing aid (E) based on 100 parts by mass of the copolymer (A).

8. The composition for a transmission belt according to claim 1 , further comprising a crosslinking auxiliary (F).

9. The composition for a transmission belt according to claim 1, further comprising a trans-polyoctenylene.

10. The composition for a transmission belt according to claim 1, further comprising a modified polybutadiene.

11. A molded article formed from the composition for a transmission belt according to any one of claims 1 to 10.

12. A power transmission belt comprising the molded article according to claim 11.

13. A crosslinked molded article formed from the composition for a transmission belt according to any one of claims 1 to 10.

14. A power transmission belt comprising the crosslinked molded article according to claim 13.

Citation Information

Patent Citations

  • Short fiber reinforced elastomer composition for transmission belt and transmission belt

    JP2001310951A

  • Friction transmission belt

    JP2012215212A